Modern Trends in Antarctic Researches (Scientometric Analysis) - Videnina, N. G. (Ukrainian Antarctic Journal, 2005)
Modern trends of Antarctic research activities are studied by bibliometric techniques. Sources of bibliographic data include thematic electronic databases Cold Regions Bibliography (Library of U.S. Congress), Antarctic Bibliography (American Geological Institute), and search engine for scientific information Scirus, being available for online searching. Their comparative assessments and arguments “for” using the search engine Scirus for scientometric analysis are given. It is shown, that foreign scientific Antarctic publications, indexed in Scirus, is an integral informational channel in the world system of scolarly communication. On the basis of received bibliometric data it is shown, that scientific research in the Antarctic Peninsula region is one of key components of scientific activities of countries in Antarctica. Out of all geographic regions of Antarctica, the most common ones in scientific publications are Southern Ocean (20 % of bibliographic records), Indian Ocean (13 %), Weddell Sea (11 %), and Antarctic Peninsula (8 %). Total share of scientific articles on main geographical objects in the region of Antarctic Peninsula makes up almost one third of total number of scientific publications, devoted to Antarctic researches, and this number grows. During last 10 years, their number increased by 10–40 % except such scientific fields as medicine, meteorology and glaciology. Assessment of size and dynamics of growth of bibliographic data by environmental research directions results in ecologization as a general tendency of countries’ activities in Antarctica. In the same time, there are significant differences of structural and dynamic characteristics of studied bibliographic databases for some countries, Antarctic geographical regions, scientific fields and areas of environmental researches.